Eye Lens Doses Received by Radiation Workers in Interventional Medical Procedures - E. Hiswara; D. Kartikasari; H. Sofyan; N. Nuraeni; K.Y.P. Sandy (Atom Indonesia, 2020)
The International Commission on Radiological Protection (ICRP) has recently recommended that the occupational dose limit for the eye lens be reduced to 20 mSv per year, averaged over defined periods of 5 years, with no single year exceeding  50 mSv. ICRP clearly states that the recommendations are chiefly based on epidemiological evidence that suggested the eye lens dose threshold for cataract induction revised downwards from 2-5 Gy to about 0.5 Gy. Interventional medical workers are at greater health risk from radiation exposure to eyes as a result of the procedures they undertake than most other medical specialists. An extensive study has been carried out to measure the eye lens doses received by 373 interventional medical radiation workers in twelve large hospitals in Indonesia. Measurements were made using Thermo Scientific Harshaw thermoluminescence dosimeter (TLD) chip (size 3.2 mm × 3.2 mm × 0.15 mm) put inside an EYE-D holder placed in the worker’s temple. The procedures performed are grouped based on classification made by the UNSCEAR (United Nations Scientific Committee on the Effects of Atomic Radiation). The results showed that in general the measured data are in an agreement with some published data, even though a large range of doses was observed. The highest mean eye lens dose of 0.2378 mSv per procedure was received by interventionists who worked in the abdominal interventions procedure. Overall, from the results of measurement, it can be concluded that most interventionists might receive eye lens dose exceeding the dose limit if the procedures are carried out on daily basis, and the abdominal interventions procedures were found to be the ones that give the highest risk to the eye lens of workers as it delivered the highest dose to this particular organ.